2019
DOI: 10.20965/jrm.2019.p0329
|View full text |Cite
|
Sign up to set email alerts
|

Using Uncertain DM-Chameleon Clustering Algorithm Based on Machine Learning to Predict Landslide Hazards

Abstract: Landslide hazard prediction is a difficult, time-consuming process when traditional methods are used. This paper presents a method that uses machine learning to predict landslide hazard levels automatically. Due to difficulties in obtaining and effectively processing rainfall in landslide hazard prediction, and to the existing limitation in dealing with large-scale data sets in the M-chameleon algorithm, a new method based on an uncertain DM-chameleon algorithm (developed M-chameleon) is proposed to assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Rainfall factor was also selected because frequent rain waters can easily penetrate the soils due to sinkholes, loess structural joints, and weathering fractures, forming saturated areas on impermeable layers, which leads to a reduction in soil strength and gravity, creating pore water pressure and increase in the weight of the rocks and soil mass. The selection of this factor is also supported by the historic reports that recorded the frequency of landslide events during the rainy season (Zhang and Liu, 2010;Hu et al, 2019). Figure 4A-G represents the thematic maps for the factors whereby: maps for elevation, slope angle, slope aspect, and profile curvature were generated from DEM at a 25 m resolution and a scale of 1:10,000, NDVI and lithology maps were developed from ETM + remote sensing images, and geology map at a scale of 1: 50,000 respectively, and the rainfall map was created based on meteorological data at a scale of 1:50,000.…”
Section: Landslide Conditioning Factorsmentioning
confidence: 75%
See 4 more Smart Citations
“…Rainfall factor was also selected because frequent rain waters can easily penetrate the soils due to sinkholes, loess structural joints, and weathering fractures, forming saturated areas on impermeable layers, which leads to a reduction in soil strength and gravity, creating pore water pressure and increase in the weight of the rocks and soil mass. The selection of this factor is also supported by the historic reports that recorded the frequency of landslide events during the rainy season (Zhang and Liu, 2010;Hu et al, 2019). Figure 4A-G represents the thematic maps for the factors whereby: maps for elevation, slope angle, slope aspect, and profile curvature were generated from DEM at a 25 m resolution and a scale of 1:10,000, NDVI and lithology maps were developed from ETM + remote sensing images, and geology map at a scale of 1: 50,000 respectively, and the rainfall map was created based on meteorological data at a scale of 1:50,000.…”
Section: Landslide Conditioning Factorsmentioning
confidence: 75%
“…The average annual temperature and rainfalls are 10 °C and 550 mm respectively, and the heavy rainfall varies between 58 and 117 mm extending between June and October (Zhang and Liu, 2010). It has also been observed that rainfall triggers most landslides in the area (Mao et al, 2017;Hu et al, 2019;Mao et al, 2021a).…”
Section: The Study Areamentioning
confidence: 99%
See 3 more Smart Citations